Highly Water‐Dispersible Surface‐Modified Gd2O3 Nanoparticles for Potential Dual‐Modal Bioimaging. Issue 38 (28th August 2013) - Hu, Zhangjun; Ahrén, Maria; Selegård, Linnéa; Skoglund, Caroline; Söderlind, Fredrik; Engström, Maria; Zhang, Xuanjun; Uvdal, Kajsa
Abstract Water‐dispersible and luminescent gadolinium oxide (GO) nanoparticles (NPs) were designed and synthesized for potential dual‐modal biological imaging. They were obtained by capping gadolinium oxide nanoparticles with a fluorescent glycol‐based conjugated carboxylate (HL). The obtained nanoparticles (GO‐L) show long‐term colloidal stability and intense blue fluorescence. In addition, L can sensitize the luminescence of europium(III) through the so‐called antenna effect. Thus, to extend the spectral ranges of emission, europium was introduced into L‐modified gadolinium oxide nanoparticles. The obtained EuIII‐doped particles (Eu:GO‐L) can provide visible red emission, which is more intensive than that without L capping. The average diameter of the monodisperse modified oxide cores is about 4 nm. The average hydrodynamic diameter of the L‐modified nanoparticles was estimated to be about 13 nm. The nanoparticles show effective longitudinal water proton relaxivity. The relaxivity values obtained for GO‐L and Eu:GO‐L were r1=6.4 and 6.3 s−1 mM−1 with r2/r1 ratios close to unity at 1.4 T. Longitudinal proton relaxivities of these nanoparticles are higher than those of positive contrast agents based on gadolinium complexes such as Gd‐DOTA, which are commonly used for clinical magnetic resonance imaging. Moreover, these particles are suitable for cellular imaging and show good biocompatibility.